Associations between the use of β-adrenoceptor acting drugs and the risk of dementia in older population - Cui, Shishuang; Fang, Fang; Cui, Peijing; Jiang, Qianwen; Xu, Shaoqing; Xu, Zhihong; Hu, Jia'An; Li, Feika (Frontiers in Neurology, 2022)
Objective Age-related decline within the noradrenergic system is associated with reduced cognition. The β-adrenoceptors are widely expressed in the brain as well as in the peripheral. Medications targeting β-adrenoceptor activity have been widely used in older adults. The aim of this study was to explore the associations between β-adrenoceptor acting drugs and the risk of dementia in the older population. Methods The subjects' information was collected from the electronic medical record (EMR) database. A propensity score matching strategy was conducted to select control participants for users of β2-agonists or β-antagonists. Logistic regression analysis was performed to estimate the risk of dementia with the use of β2-agonists or β-antagonists. Results A total of 1,429 participants in the EMR database were included in the study. The use of β2-agonists was strongly associated with a decreased risk of dementia [OR = 0.324, 95% confidence interval (CI): 0.149–0.707, P = 0.005]. This decreased risk showed a statistically significant inverse time-dependent pattern (Ptrend = 0.014). However, the use of non-selective β-antagonists significantly correlated with an increased dementia risk (OR = 1.961, 95% CI: 1.144–3.359, P = 0.014), although no time-dependent manner was found (Ptrend = 0.220). There was no association between selective β1-antagonists usage and dementia risk (OR = 1.114, P = 0.625). Conclusion The use of β-adrenoceptor acting drugs seems to be associated with the risk of dementia. Pharmacological interventions modulating β2-adrenoceptor activity might be a potential target in therapeutics for dementia.